High-reliability adhesive film for vehicle-mounted image display device

By adjusting the glass transition temperature and energy storage modulus of the adhesive film and using alkaline monomers, the problems of poor durability and weak UV resistance in extremely high temperature environments are solved, which significantly improves the reliability of the on-board image display device and alleviates the problem of redness of the polarizer.

CN119662144APending Publication Date: 2025-03-21SUZHOU FINESET MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411895278.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing automotive OCA glue has poor durability in extreme high temperature environments and weak UV resistance. It is also prone to local redness problems in high temperature reliability tests.

Method used

The adhesive film with a glass transition temperature controlled between -25 and -15℃, an energy storage modulus at 25℃, between 75,000Pa and 100,000Pa at 1Hz, and an energy storage modulus of 0.1Hz of 120℃ is greater than 30,000Pa, and alkaline monomers are included in the raw material.

Benefits of technology

It improves the reliability of the adhesive film in high temperature environments, alleviates the problem of polarizer redness, and enhances the resistance to ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a high-reliability adhesive film for a vehicle-mounted image display device, the glass transition temperature of the adhesive film is controlled between-25 DEG C and-15 DEG C, and the storage modulus of the adhesive film at 25 DEG C and 1 Hz is 75000-100000 Pa; the storage modulus of the adhesive film at 120 DEG C and 0.1 Hz is greater than 30000 Pa, and the raw materials of the adhesive film comprise alkaline monomers. The adhesive film has the advantages of being good in display effect and excellent in reliability when matched with vehicle-mounted equipment in the using process, and meanwhile the problem that a polaroid turns red after a high-temperature reliability test can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical adhesives, and in particular to an adhesive film for a highly reliable vehicle-mounted image display device. Background Art

[0002] OCA glue is a transparent adhesive widely used in the automotive field, especially for bonding car display screens. In the prior art, in order to improve the high temperature resistance of OCA glue, heat-resistant agents or high temperature-resistant fillers are generally added to enhance the thermal stability of OCA glue; in addition, there are also some technologies that use double-sided tape to combine OCA glue with other high temperature adhesives to improve the overall high temperature resistance. Although such solutions have improved the high temperature resistance of OCA glue to a certain extent, there are still the following problems: First, the existing technology still cannot meet the needs of some special high temperature environments, such as extremely hot climates or high temperature engine compartments; second, the anti-ultraviolet (UV) ability of vehicle-mounted OCA glue is relatively weak, and long-term exposure to ultraviolet rays will cause aging and performance degradation of the adhesive; finally, OCA is currently equipped with polarizers from different manufacturers, and local redness occurs in high temperature reliability tests. In order to deal with this problem, manufacturers usually bake the polarizers to deal with the redness problem, which greatly affects production efficiency.

[0003] CN 117820976 A reports the use of oligomeric organosilicon to modify acrylic prepolymers, and the use of bulk polymerization to synthesize an oligomer having the advantages of both organosilicon and acrylic resins to prepare silicon-containing OCA, with the aim of improving the poor weather resistance of vehicle-mounted OCA. However, the adhesion to the substrate is weak, and defects are easily encountered in the bonding process.

[0004] CN 116333653 A reports an OCA optical adhesive for bonding vehicle-mounted display screens, wherein a large amount of nitrogen-containing acrylic functional monomers are added to the main material, with the aim of providing the product with excellent heat resistance, high temperature and high humidity resistance, and bonding performance. However, a large amount of N-atom-containing acrylic functional monomers will affect the aging optical properties of OCA, and in particular, will make it more prone to yellowing in light and high temperature reliability tests.

[0005] CN115717036A reports a UV-curable polyurethane acrylate OCA optical adhesive, which uses polyurethane acrylate with a special weight-average molecular weight and glass transition temperature to react with hydroxyl acrylate monomers and aliphatic acrylate monomers to form a compact three-dimensional network structure, thereby improving the adhesive layer's adhesion, weather resistance, resistance to yellowing due to aging, and light transmittance. However, polyurethane OCA often performs poorly in harsh reliability tests such as high temperature and humidity and sunlight exposure.

[0006] Therefore, how to solve the above technical problems is the research direction that technicians in this field are committed to. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a highly reliable adhesive film for a vehicle-mounted image display device, which effectively alleviates the reddening problem of a high-temperature reliable rear polarizer.

[0008] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a highly reliable adhesive film for a vehicle-mounted image display device, the glass transition temperature of the adhesive film is controlled between -25 and -15°C, and the storage modulus at 25°C and 1Hz is between 75000Pa and 100000Pa; the storage modulus at 120°C and 0.1Hz is greater than 30000Pa, and the raw materials of the adhesive film contain alkaline monomers.

[0009] As a specific implementation manner, the raw materials of the adhesive film include the following components in parts by weight:

[0010] 1) 90-100 parts of an acrylic acid derivative polymer, wherein the acrylic acid derivative polymer comprises the following raw materials based on 100% by mass: 80%-90% of a C4-C18 acrylic acid ester monomer, 10%-17% of a hydrophilic monomer, and 1%-5% of a basic monomer;

[0011] 2) 0.1-1 part of a photoinitiator without a carbon-carbon double bond group, wherein the photoinitiator is a hydrogen abstraction type photoinitiator or a cleavage type photoinitiator.

[0012] As a specific implementation, the photoinitiator is 1,6-hexanediol diacrylate.

[0013] As a specific implementation, the C4-C18 acrylic acid ester monomer uses isooctyl acrylate and isooctyl methacrylate, the addition amount of isooctyl acrylate accounts for 70% or more of the acrylic acid derivative polymer raw material, and the addition amount of isooctyl methacrylate accounts for 5-10% of the acrylic acid derivative polymer raw material.

[0014] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: the glass transition temperature of the adhesive film of the present invention d is controlled between -25 and -15°C, and the storage modulus at 25°C and 1Hz is between 75000Pa and 100000Pa; the storage modulus at 120°C and 0.1Hz is greater than 30000Pa, and the raw materials of the adhesive film contain alkaline monomers. This makes the adhesive film have the advantages of good display effect and excellent reliability when used with vehicle-mounted equipment, and can also alleviate the problem of reddening of polarizers after high-temperature reliability testing. DETAILED DESCRIPTION

[0015] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0016] The present invention provides an adhesive film for a highly reliable vehicle-mounted image display device, wherein the glass transition temperature of the adhesive film is controlled between -25 and -15°C, and the storage modulus at 25°C and 1 Hz is between 75000 Pa and 100000 Pa; the storage modulus at 120°C and 0.1 Hz is greater than 30000 Pa, and the raw materials of the adhesive film contain alkaline monomers.

[0017] The raw materials of the adhesive film include the following components by weight:

[0018] 1) 90-100 parts of an acrylic acid derivative polymer, wherein the acrylic acid derivative polymer comprises the following raw materials based on 100% by mass: 80%-90% of a C4-C18 acrylic acid ester monomer, 10%-17% of a hydrophilic monomer, and 1%-5% of a basic monomer;

[0019] 2) 0.1-1 part of a photoinitiator without a carbon-carbon double bond group, wherein the photoinitiator is a hydrogen abstraction type photoinitiator or a cleavage type photoinitiator.

[0020] Example 1

[0021] In a reaction container equipped with a thermometer, a stirrer and a nitrogen injection tube, 74.0 g of isooctyl acrylate, 10.0 g of isooctyl methacrylate, 13.0 g of hydroxyethyl acrylate, 3.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 14%. Then, 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0022] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for adhesive sheet was applied into a sheet by a roller, and ultraviolet rays were irradiated by an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0023] Example 2

[0024] In a reaction container equipped with a thermometer, a stirrer and a nitrogen injection tube, 78.0 g of isooctyl acrylate, 6.0 g of isooctyl methacrylate, 13.0 g of hydroxyethyl acrylate, 3.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 14%, and then 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added. After stirring and dissolving evenly, the mixture was degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0025] Thereafter, the adhesive resin composition for an adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for an adhesive sheet was applied into a sheet form using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0026] Example 3

[0027] In a reaction container equipped with a thermometer, a stirrer and a nitrogen injection tube, 74.0 g of isooctyl acrylate, 6.0 g of isooctyl methacrylate, 17.0 g of hydroxyethyl acrylate, 3.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 14%, and then 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added. After stirring and dissolving evenly, the mixture was degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0028] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for adhesive sheet was applied into a sheet by a roller, and ultraviolet rays were irradiated by an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0029] Comparative Example 1

[0030] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 84.0 g of isooctyl acrylate, 13.0 g of hydroxyethyl acrylate, 3.0 g of acrylamide, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 14%. Then, 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0031] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for adhesive sheet was applied into a sheet by a roller, and ultraviolet rays were irradiated by an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0032] Comparative Example 2

[0033] In a reaction container equipped with a thermometer, a stirrer and a nitrogen injection tube, 56.0 g of isooctyl acrylate, 25.0 g of isooctyl methacrylate, 14.0 g of hydroxyethyl acrylate, 5.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 14%. Then, 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0034] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for adhesive sheet was applied into a sheet by a roller, and ultraviolet rays were irradiated by an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0035] Comparative Example 3

[0036] In a reaction container equipped with a thermometer, a stirrer and a nitrogen injection tube, 64.0 g of isooctyl acrylate, 10.0 g of isooctyl methacrylate, 13.0 g of isobornyl acrylate, 13.0 g of hydroxyethyl acrylate and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The polymer was polymerized under 365nm LED light to increase the solid content to 14%.

[0037] 0.4 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were further added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0038] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition), and the adhesive resin composition for adhesive sheet was applied into a sheet by a roller, and ultraviolet rays were irradiated by an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0039] The adhesive sheets obtained in the above examples and comparative examples were evaluated according to the following evaluation method. The evaluation results are shown in Table 1.

[0040] (I) Determination of glass transition temperature, loss elastic modulus and storage elastic modulus

[0041] An adhesive sheet with a thickness of 0.5 mm, a width of 10 mm, and a length of 10 mm was prepared and measured using a wide range dynamic viscoelasticity measuring apparatus (Solids Analyzer RSA-II, manufactured by Pheometric Scientific) in a share sandwich mode, at a frequency of 1.0 Hz, a measuring temperature range of -40 to 80°C, and a heating rate of 5°C / min.

[0042] (II) Determination of storage modulus at 25°C and 1Hz

[0043] An adhesive sheet with a thickness of 0.5 mm, a width of 10 mm, and a length of 10 mm was prepared and measured using a wide range dynamic viscoelasticity measuring device (Solids Analyzer RSA-II, manufactured by Pheometric Scientific) in Frequencyscan mode at a temperature of 120°C and a frequency range of 0.01 Hz-10 Hz. The storage modulus corresponding to 1 Hz was used as the standard.

[0044] (III) Determination of storage modulus at 120°C and 0.1 Hz

[0045] An adhesive sheet with a thickness of 0.5 mm, a width of 10 mm, and a length of 10 mm was prepared and measured using a wide range dynamic viscoelasticity measuring device (Solids Analyzer RSA-II, manufactured by Pheometric Scientific) in Frequencyscan mode at a temperature of 120°C and a frequency range of 0.01 Hz to 10 Hz. The storage modulus corresponding to 0.1 Hz was used as the standard.

[0046] (IV) Lighting test

[0047] The prepared adhesive sheet (film thickness is 250μm) is attached to the glass cover plate of the mobile phone (ink step difference is 30μm) according to the appropriate size, and is pasted with a rubber roller (roller diameter: 50mm, roller width: 210mm) at a load of 2kg at 25°C and atmospheric pressure. Next, the display module and the glass cover plate are bonded in a laminating machine (Yogawa TPL-0512MH), and the laminating conditions are room temperature, 1000Pa, and the pressing conditions are 0.2MPa, 10s. After that, degassing is carried out for 15 minutes at 55°C and 0.4MPa, and it is left to stand at room temperature for 24 hours. After lighting up, observe whether yellow spots or yellowing of the edges will appear in the white screen state. If so, it is NG, otherwise it is passed.

[0048] (V) Reliability evaluation

[0049] Reliability refers to the ability of the finished product to withstand bubbles, floating, and peeling under different environmental conditions after the film is attached. The specific evaluation method is as follows:

[0050] The OCA (glass-adhesive film-display module) assembly of the present invention is placed under the conditions of 85°C and 85% RH for 1000 hours, and then cooled to room temperature to observe whether bubbles appear. If bubbles appear, it is considered as defective, otherwise it is recorded as passed. The mold is lit to observe whether there is a red area in the screen. If there is, it is considered as Pol red. If there is no color difference in the display area, it is passed.

[0051] Table 1

[0052]

[0053] It can be seen from the above table that when the glass transition temperature is lower than -25°C and the storage modulus at 25°C 1Hz is lower than 75000Pa, such as Comparative Example 1, bubbles appear in the product after being placed at 85°C and 85% RH for 1000 hours; when the glass transition temperature is higher than -15°C and the storage modulus at 25°C 1Hz is higher than 100000Pa, such as Comparative Document 2, the lighting test fails; when the raw material does not contain alkaline monomers, such as Comparative Example 3, the product obtained has a red area in the screen when the mold is lit.

[0054] When the adhesive film meets the requirements of glass transition temperature between -25℃ and -15℃; storage modulus at 25℃1Hz is between 75000Pa and 100000Pa; storage modulus at 120℃0.1Hz is greater than 30000Pa; and the raw materials contain alkaline monomers, it can ensure that during the product lighting test, no yellow spots or yellowing of edges will appear in the white screen state, and the redness problem of polarizer in reliability test can be alleviated.

[0055] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly reliable adhesive film for a vehicle-mounted image display device, characterized in that: The glass transition temperature of the adhesive film is controlled between -25 and -15°C, and the storage modulus at 25°C and 1 Hz is between 75000 Pa and 100000 Pa; the storage modulus at 120°C and 0.1 Hz is greater than 30000 Pa, and the raw materials of the adhesive film contain alkaline monomers.

2. The highly reliable adhesive film for a vehicle-mounted image display device according to claim 1, characterized in that: The raw materials of the adhesive film include the following components by weight: 1) 90-100 parts of an acrylic acid derivative polymer, wherein the acrylic acid derivative polymer comprises the following raw materials based on 100% by mass: 80%-90% of a C4-C18 acrylic acid ester monomer, 10%-17% of a hydrophilic monomer, and 1%-5% of a basic monomer; 2) 0.1-1 part of a photoinitiator without a carbon-carbon double bond group, wherein the photoinitiator is a hydrogen abstraction type photoinitiator or a cleavage type photoinitiator.

3. The highly reliable adhesive film for a vehicle-mounted image display device according to claim 2, characterized in that: The photoinitiator used is 1,6-hexanediol diacrylate.

4. The highly reliable adhesive film for a vehicle-mounted image display device according to claim 2, characterized in that: The C4-C18 acrylic acid ester monomers include isooctyl acrylate and isooctyl methacrylate, wherein the amount of isooctyl acrylate added accounts for 70% or more of the acrylic acid derivative polymer raw material, and the amount of isooctyl methacrylate added accounts for 5-10% of the acrylic acid derivative polymer raw material.

Citation Information

Patent Citations

  • OCA adhesive film for bonding vehicle-mounted display screen and preparation method of OCA adhesive film

    CN117820976A

Cited By

  • Acrylate adhesive film with high weather resistance as well as preparation method and application thereof

    CN120519101A